Trade Liberalization in a Globalizing World - Riccardo Faini (Institute for the Study of Labor (IZA), 2004)
Globalization is not only about the rise of trade, FDI, and migration. It is also about the changing linkages among these flows. The main findings of the paper can be summarized as follows. First, at least in the nineties, import trade liberalization fostered not only trade but also inward investment, confirming that trade and FDI toward developing countries have become largely complements. Second, the presence of a skilled labour force is a relevant factor to attract FDI. Moreover, trade policies and the stock of FDI have a positive impact on the incentives to invest in education. This set of findings highlights the possibility of a low equilibrium trap where the lack of human capital discourages FDI and inadequate investment from abroad limits the domestic incentives to acquire education. Rich countries, by encouraging skilled immigration from relatively poor countries, are definitely aggravating such a risk. Third, we find little evidence supporting the contrary argument of a brain gain, where the possibility for skilled workers to migrate abroad raises the return to education and the investment in human capital. Overall, our results highlight the need to study globalization in a fully integrated way, not just as the sum of its different components. They also show that backtracking in one area (e.g. trade) feeds negatively on other areas (e.g. FDI).
Keywords: F22; F23; 330; FDI; migration; trade; Aussenhandelsliberalisierung; Globalisierung; Direktinvestition; Internationale Arbeitsmobilität; Facharbeiter; Brain Drain; Welt